https://doi.org/10.36873/agp.v20: PENGARUH KONSORSIUM AGENS HAYATI DAN JARAK TANAM TERHADAP KEJADIAN PENYAKIT BUSUK PUTIH (Sclerotium cepivorum Berk.) PADA BAWANG DAUN Influence of The Consortium of Biological Agents and Spacing to White Rot Disease (Sclerotium cepivorum Berk.) of Scallio, Mulyani, R. B.,*1), Djaya, A. A., 1) dan Zubaidah, S. 1) - Admin journal (AgriPeat, 2019)
ABSTRACTThis study aims to determine effective management patterns to control Sclerotium rot and to improvepeat soil fertility with the application of the Trichoderma sp + Aspergillus sp consortium.as biologicalagents and P solvents, combined with spacing arrangements in the cultivation of scallion in peatlands.The study used a factorial randomized block design consisting of two factors with four replications.Factor I Application of biological agents consists of: A0 = No biological agents; A1 = Consortium ofTrichoderma sp. + Aspergillus sp; Factor II Plant spacing, consisting of J1 = 20x25 cm; J2 = 25x25cm and J3 = 30x25 cm. The results showed that the interaction treatment of Trichoderma sp. +Aspergillus sp. and spacing of 25x25 cm effectively suppresses the incidence of white rot disease(Sclerotium cepivorum Berk) up to 34.02%, while at a spacing of 20x25 cm with the application ofTrichoderma sp. + Aspergillus sp. produced the highest fresh plant weight of 8.80 kg plot-1 or 24.44tons hectares-1. Increasing the number of leaves is only influenced by a single factor of biologicalagents (23.29%) and spacing of 25x25 cm (19.7%). Application of Trichoderma sp. + Aspergillus sp.can increase the nutrient content of N, P (total and available), K and peat soil organic matter.Consortium of biological agents Trichoderma sp. and Aspergillus sp. indigenous have the potential tobe developed as biological agents and biofertilizers, with optimum spacing can be applied to themanagement of scallion cultivation in peatlands.Key words: Sclerotium cepivorum Berk, scallion, Trichoderma sp. and Aspergillus sp., spacing